Supercomputers: Influencing Tomorrow's General-Purpose Hardware - Gitomer, Jerry (The Journal of information systems management, 1986)
By studying state-of-the-art supercomputers, MIS managers can estimate the state of the typical commercial data processing installation five to ten years from now. This enables them to plan more knowledgeably, resulting in information systems that are more responsive to their organizations' needs.